Women’s visibility at European Society for Clinical Nutrition and Metabolism congresses from 2011 to 2019: Is the floor yours? - Occhiali, Emilie; Demailly, Zoe; Clavier, Thomas; Achamrah, Najate (Frontiers in Nutrition, 2022)
Purpose: Participating in international conferences is an essential way to promote scholarly work. We aimed to assess the trend of women’s visibility at the European Society for Clinical Nutrition and Metabolism (ESPEN) congress by describing the evolution of the proportion of women speakers between 2011 and 2019. Methods: This is a retrospective study including public data obtained from the 2011, 2015 and 2019 ESPEN congresses. The primary endpoint was the percentage of women speakers in major oral sessions (oral communications and specific conferences including prestigious lectures). The secondary endpoints were the proportion of women in other high-visibility positions (moderators, industry-led symposia interventions) and countries of origin. Results: The proportion of women speakers in oral communications remained stable between 2011 and 2019 (43% (43/100) vs 41% (46/111), respectively; p=0.89). The proportion of women moderators in oral communications sessions significantly increased between 2011 and 2019 (13% (6/45) vs 41% (19/46), respectively; p=0.004). The percentage of women speakers and moderators in industry-led symposia significantly increased between 2011 and 2019 (11% (2/18) vs 41% (11/27), p=0.05; 0% (0/6) vs 60% (6/10), p=0.03, respectively). The percentage of women speakers in educational sessions remained stable between 2011 and 2019 (34% (19/56) vs 36% (30/84); p=0.88). The percentage of women moderators in educational sessions also remained stable during the period with a marked under-representation of women in 2015. During all three congresses, women from the host countries were over-represented as moderators compared to women from other countries. Conclusion: The percentage of women speakers in oral communications remained stable in the last 8 years at ESPEN congresses, although women’s representation in other high-visibility positions has increased. As men remained over-represented, women should be more encouraged to promote their academic work in the field of Nutrition, particularly during this international congress.